Spectroscopic studies of hydrogen plasmas in a magnetic well - Steyn, Douw G (Department of Physics, 2016)
Experiments are described in which the containment times of plasmas in Andreoletti's modified theta-pinch apparatus are increased by the addition of an external D.C. field produced by a modified version of the "Tennis Ball Seam" conductor described by Larkin. The diagnostics used are all spectroscopic.